KEDUDUKAN KHUNTHA DALAM UNDANG-UNDANG PUSAKA ISLAM - Muda, Mohd Zamro (Jurnal Syariah, 2019)
The article explains the position of khunth71 in the Islamic law of inheritance. The focus is given on the opinion of scholars of the sunnt school and its solving method of division of khunthii ’s inheritance. As a result, the muslim scholars differ on determining the right proportion of khunth71’s inheritance. However, the assured condition of khuntha is determining factor in dividing the inheritance.